2001
DOI: 10.1002/jbt.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium and Aluminum Intake on the Antioxidant Status and Lipid Peroxidation in Rat Tissues

Abstract: This work aimed to study the relationship between the accumulation of cadmium (Cd) or aluminum (Al) in certain tissues and the levels of lipid peroxides as well as tissue antioxidants. To carry out such investigations, CdCl2 was given to rats in two dose levels; 0.5 or 2.0 mg/kg i.p for 1 day or daily repeated doses for 2 weeks. Al was given as AlCl3 either in a single dose of 100 mg/kg or daily repeated doses of 20 mg/kg for 2 and 4 weeks. The measured parameters were tissue malondialdehyde (MDA, index of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 38 publications
6
29
2
Order By: Relevance
“…It is well-known that cellular GSH redox status is affected by Cd action (41,42). This, however, is questioned by the results of our and other studies in which Cd had no effect on cellular GSH redox status (43,44). Thijssen et al (44) reported that the treatment of mice with 100 mg L -1 Cd had no effect liver and kidney GSH and GSSG levels, and that cellular redox status was protected by elevated metallothionein levels, which are important in Cd detoxification.…”
Section: Discussioncontrasting
confidence: 83%
“…It is well-known that cellular GSH redox status is affected by Cd action (41,42). This, however, is questioned by the results of our and other studies in which Cd had no effect on cellular GSH redox status (43,44). Thijssen et al (44) reported that the treatment of mice with 100 mg L -1 Cd had no effect liver and kidney GSH and GSSG levels, and that cellular redox status was protected by elevated metallothionein levels, which are important in Cd detoxification.…”
Section: Discussioncontrasting
confidence: 83%
“…The activities of ALT, AST and ALP in the serum of rats are tested as indicator for hepatic function [13,14]. In our study, the activities of ALT and AST in the serum of cadmium exposed rats were significantly elevated, and the activity of ALP was significantly decreased indicating Cd-related injury to the liver.…”
Section: Discussionmentioning
confidence: 48%
“…Aluminum sulfate, which is the preferred form of aluminum salt in our study, was selected due to the fact that it is the most absorbed form of Al salt by the small intestine, as determined by Cunat et al (2000). El-Maraghy et al (2001) found that, after injecting aluminum salt into rats, there was a 35% increase in the Al level of hepatic tissue, whereas serum Al levels contained 209% more Al than the normal values. Khattab (2007) observed histological damage and loss of tissue in the testicles after injecting aluminum sulfate into rats.…”
Section: Discussionmentioning
confidence: 93%